EL sacrificio televisado: a propósito de "las decapitaciones on-line": La representación de un drama trágico sacrificial, y el papel de los medios en esta construcción - García Hernández, Fernando Rubén (Nómadas. Critical Journal of Social and Juridical Sciences, 2005)
The object of this paper is to present the Death´s Constructive Process using Mass-Media by Islamic terrorists: the transformation of an individual fact ( prisoner´s beheading) in an ontological and political phenomenon (becalm Divinity´s Anger and give back to the previous political pre-sort).